2009
DOI: 10.1016/j.elecom.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Performance of plasma sputtered fuel cell electrodes with ultra-low Pt loadings

Abstract: Ultra-low Pt content PEMFC electrodes have been manufactured using magnetron cosputtering of carbon and platinum on a commercial E-Tek ® uncatalyzed gas diffusion layer in plasma fuel cell deposition devices. Pt loadings of 0.16 and 0.01 mg cm -2 have been realized.The Pt catalyst is dispersed as small clusters with size less than 2 nm over a depth of 500 nm.PEMFC test with symmetric electrodes loaded with 10 µg cm -2 led to maximum reproducible power densities as high as 0.4 W cm -2 and 0.17 W cm -2 with Nafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 22 publications
2
67
0
3
Order By: Relevance
“…For example, a simultaneous co-sputtering of carbon and platinum on a conventional carbon porous substrate led to high electrodes efficiency for both the hydrogen oxidation and oxygen reduction reactions. The PEMFC tested in this case achieved a specific power of 20 kW per 1 g of platinum, which is one of the best results reported so far (Cavarroc et al, 2009). Carbon and platinum can be also deposited by subsequent sputtering processes.…”
Section: Catalytic Electrodes For Fuel Cellssupporting
confidence: 55%
“…For example, a simultaneous co-sputtering of carbon and platinum on a conventional carbon porous substrate led to high electrodes efficiency for both the hydrogen oxidation and oxygen reduction reactions. The PEMFC tested in this case achieved a specific power of 20 kW per 1 g of platinum, which is one of the best results reported so far (Cavarroc et al, 2009). Carbon and platinum can be also deposited by subsequent sputtering processes.…”
Section: Catalytic Electrodes For Fuel Cellssupporting
confidence: 55%
“…Previous successful attempts were concerned with the use of carbon nanotubes [20] or nanofibers [21], keeping a power mass density in the range 2-5 kW gPt -1 . It has also to be noted that cell performance we obtained previously (400 mA cm -2 with electrodes loaded at 0.01 mg cm -2 platinum [5]) were improved…”
Section: Performance Of Catalyst Under Pemfc Conditionsmentioning
confidence: 55%
“…Then we will present and discuss the results obtained under PEMFC working conditions with a fuel cell fitted with a Nafion 212 membrane and high performance electrodes with ultra-low Pt loading down to 0.01 mg cm -2 ( Fig. 1), leading to 20 kW.g Pt -1 [5]. Analysis by Rutherford Backscattering Spectroscopy (RBS) has shown that the platinum density depth profile inside the diffusion layer is a key parameter to explain such a high efficiency [5].…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The durability of a PEM fuel cell relies mainly on the characteristics of the membrane electrode assembly (MEA), while the reduction in cost critically depends on enhancing the performance of the MEAs while minimizing the Pt content. The lowering of the platinum loading on the electrodes has become the subject of much research [2][3][4]. Platinum comprises a large portion of the PEMFC"s cost due to its high price and limited supply.…”
Section: Introductionmentioning
confidence: 99%